Improving Student Learning Achievement through Group Guidance in Natural and Social Sciences Subjects at MI Maraqitta'limat Lengkok Lendang - Harsini (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to investigate the effectiveness of group counseling in improving student achievement in the subject of Natural and Social Sciences at MI Maraqitta’limat Lengkok Lendang. The research is grounded in the growing need for innovative educational approaches that address not only academic content but also students’ motivation, collaboration skills, and personal development. Utilizing a classroom action research (CAR) method, the study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were fifth-grade students who demonstrated low academic performance and limited participation in classroom activities. Data collection methods included tests, observations, field notes, and student interviews. The results indicate a significant improvement in student learning outcomes after the implementation of group counseling. In Cycle I, only 56% of students reached the minimum competency standard, whereas in Cycle II, this number increased to 87%. Furthermore, qualitative data revealed an increase in students’ motivation, self-confidence, and ability to work cooperatively with peers. The findings suggest that group counseling is an effective strategy to enhance not only academic achievement but also affective and social aspects of learning. Therefore, it is recommended that educators consider incorporating group counseling techniques into their teaching practices, especially in subjects that require critical thinking and interpersonal skills. This research contributes to the broader discourse on holistic education and offers practical implications for teachers, school counselors, and educational policymakers aiming to foster inclusive and supportive learning environments.